Development and Application of a 3D Coding Environment for Mathematics Learning - Inyong Choi (Korea Society of Educational Studies in Mathematics, 2020)
In this study, we developed a 3D coding learning environment for integrated learning of mathematics and CT, and presented a teaching-learning plan that can be used in theme selection activities of the free-semester. First, based on the design theory of constructionism, we developed a 3D game-making environment 〈MathCraft〉 that can build structures with small cube blocks and implement interactive game elements through coding. Using this concept, we developed free-semester teaching-learning content in the form of game-making that included mathematics learning elements in the middle school curriculum and applied it to 40 students and 20 math teachers. As a result, the developed environment and free-semester program provided students with valuable learning opportunities in mathematics and CT, and had positive impact on improving the affective characteristics of mathematics and coding. Based on the application results, the learning environment and teaching-learning content were corrected and supplemented. Based on the research process and the results, implications for the integrated education of mathematics and CT using coding are suggested.